Analisis Karakteristik Anak Tidak Bersekolah di Indonesia - Fahmi, Mohamad; Marizka, Demy (Jurnal Ekonomi dan Pembangunan Indonesia, 2014)
This research identified and analyzed school participation of children in Indonesia from 7 to 15 years old. Using data collected by Survey Sosial Ekonomi Nasional (SUSENAS) in 2012, probit model estimates that there are more probabilities in boys rather that girls to leave their education. As well as living environment supported, citizen have more well educated children than villagers. Elementary schools had been highly needed to fulfil school supply so that out-of-school-children level will drop as low as possible. But an increase in junior high school supplied will not turned out as it applied on elementary schools.